RESULTS OF FREQUENCY ANALYSIS OF DEFB1 GENE -44C/G rs2412971 POLYMORPHISM IN DIFFERENT FORMS OF CHRONIC TONSILLITIS - Azizkhon Z. Shaumarov; Ulugbek S. Xasanov; Jamolbek A. Djurayev (Central Asian Journal of Medicine, 2024)
In the oral cavity, the tonsils are secondary lymphoid organs, representing tissues of local immunity, capable of providing a rapid and nonspecific response to pathogens, as well as triggering the action of the acquired immune system. Despite their important role in fighting germs in the mouth, the tonsils can suffer from infections: due to their anatomical position, the tonsils are in constant contact with oral debris, foreign materials and pathogens, leading to chronic inflammation and enlargement of the tonsils. recurrent tonsillitis. Recurrent tonsillitis has a multifactorial etiology, dependent on host and environmental factors: genetic control of the innate immune system represents a possible candidate to explain, at least in part, susceptibility to the disease.